PF.43 Low Maternal Serum PAPP-A in the First Trimester and Pregnancy Outcome: An Experience Over 3 Years. (26th April 2013) - Weaver, A; Nanda, S; Rozette, C; Kyle, P; Sankaran, S
Abstract : Introduction: Maternal serum PAPP-A (pregnancy associated plasma protein-A) is a part of combined screening. Previous studies have shown correlation between low PAPP-A and adverse pregnancy outcome. Objective: The aim of this study is to establish the positive predictive value of low-PAPP-A in prediction of adverse pregnancy outcomes - pre-eclampsia (PET), pregnancy induced hypertension (PIH), delivery of small for gestational age neonates (SGA) and late pregnancy losses. Materials and Methods: 16690 women underwent combined screening from 1/8/2008 to 1/8/2011. 326 women with low PAPP-A (=<0.3 MoM) were identified (1.95%). The median PAPP-A of the screening population was 1.074 MoM. Within this group of pregnancy with low PAPP-A, maternal serum PAPP-A was compared between the subgroups of adverse pregnancy outcome and normal-outcome. Results: Conclusion: In our screening population, median PAPP-A MoM was higher compared to some previous studies. Maternal serum PAPP-A in pregnancies with adverse outcome was significantly lower than those that resulted in a normal outcome. Compared to the pregnancies with low-PAPP-A but normal outcome, median PAPP-A MoM was significantly lower in pregnancies ending in delivery of small-for-gestational age neonate (customised BW < 10 th -centile), and showed a trend towards a decrease in those ending in late-pregnancy losses (>24 weeks).